Comparative efficacy of exercise training modes on systemic metabolic health in adults with overweight and obesity: a network meta-analysis of randomized controlled trials - Wang, Huiying; Cheng, Ruitang; Xie, Lijun; Hu, Fang (Frontiers in Endocrinology, 2024)
Objective: This network meta-analysis (NMA) was conducted to compare and rank the effects of training interventions including aerobic exercise (AE), resistance training (RT), combined aerobic and resistance training (CT), and high intensity interval training (HIIT) on vital metabolic indicators in adults with overweight and obesity. Methods: PubMed, Cochrane, Embase and Web of Science were searched from 1990 to February 2023. Articles were included if they described randomized controlled trials (RCTs) of examining the effects of exercise training on anthropometry parameters, lipid profiles, glucose metabolism, blood pressure, and cardiorespiratory fitness in adults with overweight and obesity. Weighted mean difference with 95% CI were calculated.Results: 28 studies with 1620 patients were included. Results revealed that AE exerts best effects on weight loss (-2.35 [-4.05, -0.64]) and body mass index (-0.9 [-1.38, -0.42]), while HIIT is the most effective in reducing waist circumference (-5.93 [10.71, -1.15]), percentage body fat (-3.93 [-5.73, -2.12]), serum triglycerides (-20.55 [-37.20, -3.91]), fasting blood glucose (-14.31 [-22.47, -6.16]) and improving VO2 max (7.41 [4.37, 10.45]).However, no significant benefit was observed in terms of total cholesterol and blood pressure.Conclusions: AE is the optimal exercise type for reducing body weight and BMI, while HIIT exerts the most beneficial effects on improving body composition, cardiorespiratory fitness and metabolic abnormalities in adults with overweight and obesity.